Atmospheres of the inhospitable in staged kidnappings - Tzanelli, Rodanthi; Yar, Majid (Consumption, markets and culture, 2021)
This article explores the paradoxical staging of experiences of "inhospitality," taking shape as commercialised opportunities for individuals, willing to be voluntarily subjected to kidnapping. Such "extreme" leisure is facilitated by companies specialising in simulated captivities of clients. These simulations, which blend forms of performance with practices of violence, are situated theoretically within a revised iteration of Benjamin Barber's thesis about "Jihad vs McWorld." Barber's original thesis would locate such stagings within a broader tendency of contemporary capitalism to co-opt and commoditise experiences associated with "terror" and suffering. Unlike Barber, we focus on the aesthetics and atmospheres of such experiences. We aim to comprehend the ways artistic "violence experts" articulate the meaning of such leisure for subjects striving to confront and manage the risks and uncertainties of a conflict-ridden lifeworld. Resembling the schadenfreude of dark tourism and the art of performance, kidnapping packages promote a form of aesthetic education into uncertainty.